The Evaluation of Gut Microbiota in Obese Children with Primary Hypertension - Senbaykal Yigit, Ece; Gazi, Hörü; Ertan, Pelin (Klinische Pädiatrie, 2025)
The prevalence of childhood hypertension is steadily increasing, and there is growing evidence that dysbiosis of the gut microbiota plays a role in this process. This study compares the gut microbiota of children with primary hypertension to that of normotensive controls.This case-control study included 20 children with primary hypertension and 20 normotensive children matched for age, gender, and BMI. Exclusion criteria were the presence of chronic diseases other than hypertension, recent antibiotic use, and active infection. Stool samples were analyzed using 16S rRNA sequencing. Statistical analyses included Student’s t-test, Mann-Whitney U test, and FDR correction.Microbial richness was significantly reduced at all taxonomic levels in hypertensive patients. However, there were no significant differences in alpha and beta diversity indices between the groups. Levels of Bacteroidetes and Firmicutes were lower in patients, while the Firmicutes/Bacteroidetes ratio was increased (p<0.05).Changes in gut microbiota composition were observed in children with hypertension compared to the control group. These findings may enable the development of microbiota-based diagnostics and personalized treatments, and open the way for preventive approaches by identifying individuals at risk for chronic diseases.
Keywords: hypertension; microbiota; dysbiosis; Bacteroides; Firmicutes; children